Surgical management of intrathoracic wooden skewers migrating from the stomach and duodenum in dogs: 11 cases (2014–2020). (26th January 2022) - Garcia‐Pertierra, S.; Das, S.; Burton, C.; Barnes, D.; Murgia, D.; Anderson, D.; Kulendra, N.; Harris, K.; Forster, K.
Abstract : Objectives: To describe the clinical presentation, management and outcome of cases presenting with intrathoracic wooden skewers originating from the abdominal gastrointestinal tract. Materials and Methods: Clinical records of dogs presented and treated for an intrathoracic wooden skewer were reviewed from June to August 2020. Data included signalment, clinical presentation, duration of clinical signs, haematological and biochemical abnormalities, diagnostic imaging findings, surgical procedure, postoperative complications and outcome. Results: Eleven dogs were included in the study. In all cases, the foreign body was identified as a wooden skewer. The most common clinical signs were anorexia/hyporexia (n=7), vomiting/regurgitation (n=7), lethargy (n=6), pyrexia (n=4) and gait abnormalities/lameness (n=3). CT correctly identified a wooden skewer in all cases when performed (n=7). A coeliotomy combined with transdiaphragmatic thoracotomy was performed in six of 11 cases (55%), a coeliotomy combined with median sternotomy in four of 11 cases (36%) and a median sternotomy alone was performed in one case. Foreign bodies penetrated from the stomach (n=10) or the duodenum (n=1). Intrathoracic trauma was most commonly identified to the lungs (n=3) and pericardium (n=3). Complications occurred in three of 11 cases (27%), two minor and one resulting in death. Ten of the 11 cases (91%) survived to discharge. Long‐term outcome was available for seven of 11 cases (66%), all of them excellent. Clinical Significance: Despite the challenges of managing wooden skewers penetrating the thoracic cavity from the abdominal gastrointestinal tract, the majority of the patients are stable to undergo diagnostic procedures, surgical exploration and management with low morbidity and excellent short‐ and long‐term prognosis.